Evidence From Parkinson's Disease That the Superior Colliculus Couples Action and Perception. Issue 11 (21st October 2019) - Pretegiani, Elena; Vanegas‐Arroyave, Nora; FitzGibbon, Edmond J.; Hallett, Mark; Optican, Lance M.
Abstract: Background: Action and perception should be coordinated for good visual‐motor performance. The mechanism coupling action and perception may be a prominence map in the intermediate layer of the superior colliculus that modulates motor and attentional/perceptual processes. This coordination comes with a cost: the misperception that briefly overlapping stimuli are separated in time. Our model predicts that abnormal intermediate layer of the superior colliculus inhibition, such as that arising from increased basal ganglia output, would affect the action and perception coupling, and it would worsen the misperception. Objective: To test the prominence map model by measuring reaction times and perceptions in human intermediate layer of the superior colliculus dysfunction. Methods: We measured the saccadic and perceptual reaction time changes and the percept for different temporal asynchronies between fixation point offset and peripheral target onset in Parkinson's disease (PD). Results: We found that increased basal ganglia inhibitory output to the intermediate layer of the superior colliculus prominence map disrupted the normal coupling of action and perception. With increasing temporal asynchronies, the PD perceptual reaction times increased approximately 3 times more than the increase of the saccadic reaction times. Also, PD subjects misperceive small overlaps as gaps for temporal asynchronies up to 3 times longer than controls. The results can be reproduced by an intermediate layer of the superior colliculus rostral‐caudal gradient of inhibition. Conclusion: These findings support the hypothesis that a prominence map in the intermediate layer of the superior colliculus couples action and perception through modulation of attention. A dysfunction of this network quantifies abnormal basal ganglia output and could underlie visual deficits, including common, yet poorly understood, misperceptions and visual‐motor deficits of PD. © 2019 International Parkinson and Movement Disorder Society